Keberlanjutan Usaha Pedagang Warung Tradisional dengan Menerapkan Etika Bisnis Islam di Kota Makassar - M. Dzul Fadli S.; Siradjuddin Siradjuddin; Rahmawati Muin; Khaerul Aqbar (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2022)
It is important for every trader to know and apply Islamic business ethics because with it a trader can achieve the main goals of business, namely world profits and the salvation of the hereafter. This study aims to determine the understanding and application of Islamic business ethics to traditional warung traders and the role of Islamic business ethics in maintaining business sustainability. This research is a field research with qualitative method which is done descriptively. The results of this study indicate that the traditional traders understand Islamic business ethics substantially but not in detail, but most of the Islamic business ethics have been applied by traditional warung traders. Other results show that the application of Islamic business ethics in a business can maintain the business sustainability of traders. The implication of this research is to make traders aware of the importance of knowing and applying Islamic business ethics in their business.